2021
DOI: 10.1152/physiolgenomics.00104.2020
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal and integrated approach to interrogate human kidney biopsies with rigor and reproducibility: guidelines from the Kidney Precision Medicine Project

Abstract: Comprehensive and spatially mapped molecular atlases of organs at a cellular level are a critical resource to gain insights into pathogenic mechanisms and personalized therapies for diseases. The Kidney Precision Medicine Project (KPMP) is an endeavor to generate 3-dimensional (3D) molecular atlases of healthy and diseased kidney biopsies using multiple state-of-the-art OMICS and imaging technologies across several institutions. Obtaining rigorous and reproducible results from disparate methods and at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 28 publications
1
66
0
Order By: Relevance
“…If present they were tagged as possible altered states, if absent they were assessed as the final cluster. Annotations of clusters were based on known positive and negative cell type markers 10,11,[55][56][57] (also see Supplementary Table 5), regional distribution of the clusters across the corticomedullary axis and altered state (including cell cycle) features. For separation of EC-DVR from EC-AEA, the combined population was independently clustered using pagoda2 and clusters associated with medullary sampling were annotated as EC-DVR.…”
Section: Rna-sequencing Qc and Clusteringmentioning
confidence: 99%
See 2 more Smart Citations
“…If present they were tagged as possible altered states, if absent they were assessed as the final cluster. Annotations of clusters were based on known positive and negative cell type markers 10,11,[55][56][57] (also see Supplementary Table 5), regional distribution of the clusters across the corticomedullary axis and altered state (including cell cycle) features. For separation of EC-DVR from EC-AEA, the combined population was independently clustered using pagoda2 and clusters associated with medullary sampling were annotated as EC-DVR.…”
Section: Rna-sequencing Qc and Clusteringmentioning
confidence: 99%
“…Annotating snCv3 Clusters. To overcome the challenge of disparate nomenclature for kidney cell annotations, we leveraged a cross-consortium effort to use the extensive knowledge base from human and rodent single-cell gene expression data sets, as well as the domain expertise from pathologists, biologists, nephrologists and ontologists 10,11,19,[55][56][57][58] (also see Supplementary Table 4, 5 and the HuBMAP ASCT+B Reporter: hubmapconsortium.github.io/ccf-asct-reporter). This allowed the adoption of a standardized anatomical and cell type nomenclature for major and minor cell types and their subclasses (Supplementary Table 4), showing distinct and consistent expression profiles of known markers and absence of specific segment markers for some of the cell types (Extended Data Fig.…”
Section: Rna-sequencing Qc and Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that this approach could be used in archived frozen human kidney biopsies, whereby quantitation of immune cell densities could be potentially linked with other molecular or clinical features (51,53). Large scale 3D imaging and tissue cytometry of human kidney biopsy is currently being used as a main imaging technology in the Kidney Precision Medicine Project (KPMP) consortium (55,56,60).…”
Section: Profiling the Immune System With Tissue Cytometry In Experimmentioning
confidence: 99%
“…Recent kidney atlas programs have emerged with the goal of characterizing normal human tissues and discovering drivers of disease using cellular and molecular phenotypes spanning wide spatial scales and biomolecular classes. 1,2 Functional tissue units (FTUs), multicellular structures that perform vital functions, including components of the nephron in the kidney, such as glomeruli, proximal tubules, distal tubules, and collecting ducts, are an important intermediate between whole organ and individual cells. 3 Indeed, kidney diseases like diabetic nephropathy, acute kidney injury, and chronic kidney disease are a direct result of damage to the aforementioned FTUs.…”
Section: Introductionmentioning
confidence: 99%